Exploring the factors associated with prelacteal feeds in Papua New Guinea: a population-based survey - McKenzie Maviso; Elias Namosha; Georgia S. Guldan (BMJ Open)
Background Prelacteal feeding disrupts early breastfeeding initiation and exclusive breastfeeding, and increases the risk of childhood illnesses and under-five mortality. Despite its negative health outcomes, newborns are given prelacteal feeds in Papua New Guinea (PNG). This study investigated the factors associated with prelacteal feeding practices among women in PNG.Design A population-based cross-sectional study based on Demographic and Health Survey (DHS) data. Multivariable logistic regression using complex sample analysis was performed to control for the effects of potential confounders. Variables with p ≤ 0.05 were considered statistically significant.Setting Papua New Guinea.Participants A total weighted sample of 4399 women was included in the study.Outcome measure Prelacteal feeds.Results About 10% of women provided prelacteal feeds to their infants. The most frequently reported prelacteal feed was plain water (71.7%), followed by grain-based (eg, noodles) (47.1%), dark green leafy vegetables (42.1%) and soup (39.7%). Women with no formal (Adjusted Odds Ratio (AOR) 1.4, 95% CI: 1.0–3.0) or primary (AOR 1.5, 95% CI: 1.0–2.9) education, who had a caesarean section (AOR 4.1, 95% CI: 2.4–7.2), had given birth at home or in the village (AOR 3.7, 95% CI: 2.1–6.8) and from the Islands region (AOR 2.3, 95% CI: 1.5–3.5) had higher odds of providing prelacteal feeds.Conclusion Our study revealed that providing prelacteal feeds is common in PNG. Tailored health education and behaviour change communication are necessary to address this harmful infant feeding practice. Furthermore, the promotion of facility-based births and early breastfeeding practices should be prioritised using existing strategies, especially for disadvantaged and rural women.